Registered Nurses’ Perception of Pain - Rojaye, Justin Oluwasegun (Nursing and Health Sciences Journal (NHSJ), 2024)
Pain is the most common medical issue that older people face in a long-term care facility. Nurses have a critical role in helping residents manage their pain. This research looked at registered nurses’ perception of pain practices in long-term care facilities. The site for this research was a chosen long-term care facility in Ontario, Canada, a 160-bed nursing home for the elderly that provides various nursing and medical care services. A qualitative research technique was applied in this study. Semi-structured focus group interviews lasting about an hour were done. This study's population consisted of 45 nurses. The researcher chose a sample of 25 nurses using a purposive sampling strategy. The data was reviewed using qualitative data analysis to detect recurring concerns. This research revealed the necessity of identifying and overcoming registered nurses’ perception of pain practices in long-term care homes are necessary to manage pain. This study demonstrated the importance of registered nurses’ perception of pain to effectively manage pain and reinforce good practices in long-term care homes. Therefore, improved registered nurses’ perception of pain practices is required to manage pain in a long-term care home effectively. The overall benefits of registered nurses’ perception of pain practices in long-term care homes expand nurses' clinical knowledge in the care of residents living in nursing homes.